Culture Media Based on Leaf Strips/Root Segments Create Compatible Host/Organ Setup for in vitro Cultivation of Plant Microbiota - Nemr, Rahma A.; Patz, Sascha; Abdelwakeel, Saad M.; Khalil, Mohab; Ben Djadid, Ali; Abdelfadeel, Mohamed R.; Morsi, Ahmed T.; Goda, Hanan A.; Youssef, Hanan H.; Hamza, Mervat; Abbas, Mohamed; Fayez, Mohamed; et al. (Frontiers in Sustainable Food Systems, 2021)
Plant microbiota have co-evolved with their associated plants in the entire holobiont, and their assemblages support diversity and productivity on our planet. Of importance is in vitro cultivation and identification of their hub taxa for possible core microbiome modification. Recently, we introduced the in situ-similis culturing strategy, based on the use of plant leaves as a platform for in vitro growth of plant microbiota. Here, the strategy is further extended by exploring plant organ compatible cultivation of plant microbiota when grown on corresponding leaf/root-based culture media. Pooling the advantages of MPN enrichment methodology together with natural plant-only-based culture media, the introduced method efficiently constructed a nutritional milieu governed by vegan nutrients of plant origin, i.e., leaf strips/root segments, immersed in plain semi-solid water agar. MPN estimates exceeded log 7.0 and 4.0 g−1 of endo-rhizosphere and endo-phyllosphere, respectively, of maize and sunflower; being proportionate to those obtained for standard culture media. With sunflower, PCR-DGGE analyses indicated divergence in community composition of cultivable endophytes primarily attributed to culture media, signaling a certain degree of plant organ affinity/compatibility. Based on 16S rRNA gene sequencing of bacterial isolates, 20 genera comprising 32 potential species were enriched; belonged to Bacteroidetes, Firmicutes, and Alpha-/Gammaproteobacteria. The described cultivation strategy furnished diversified nutritive platform in terms of homologous/heterologous plant organ-based medium and ambient/limited oxygenic cultivation procedure. Duly, cultivability extended to > 8 genera: Bosea, Brevundimonas, Chitinophaga, Pseudoxanthomonas, Sphingobacterium Caulobacter, Scandinavium, and Starkeya; the latter three genera were not yet reported for Sunflower, and possible unknown species or even one new putative genus. Thus, both potential members of the major microbiome and rare isolates of satellite microbiomes can be isolated using the presented method. It is a feasible addition to traditional cultivation methods to explore new potential resources of PGPB for future biotechnological applications.